A Preliminary Study of Malay and Chinese Bite Mark in UKM Using Dental Wax - Wong, Lai Hong; Balkis Bashuri,; Atiah Ayunni Abd Ghani,; Nor Atika Md Ashar,; Khairul Osman, (Penerbit UKM, 2015)
Identifi cation of unknown suspect through bite marks has always been challenging. Narrowing list of suspects through sex and race markers is always recommend but rarely utilized due to limited publication in this area. Thus, this preliminary research was aimed to study the difference of bite mark made on dental wax between sex and race. A sample size of 40 UKM undergraduates comprising of Malay (male = 10, female = 10) and Chinese (male = 10, female = 10) were used in this study. Bite mark of subject was obtained through dental wax, digitally scanned and analyzed using Image-J software. Parameters measured were anterior teeth size, intercanine width and anterior teeth relative rotation. Result indicated that mandible left canine tooth size had signifi cant sexual dimorphism (p < 0.05) in differentiating sex. The means for male and female measured were 4.63 ± 1.05 mm and 5.35 ± 0.87 mm respectively. In addition to the result, tooth size of maxillary left canine and mandible left lateral incisor were signifi cantly different (p < 0.05) between races. Means for mandible left canine Malay and Chinese were 5.27 ± 1.01 mm and 4.50 ± 1.22 mm respectively. Furthermore, left lateral incisor mandible had means of 5.15 ± 0.87 mm and 4.60 ± 0.74 mm for Malay and Chinese respectively. Unfortunately, there were no signifi cant differences for intercanine width and anterior teeth relative rotation between the two major races in Malaysia. In conclusion, this research has demonstrated the possibility of using tooth size of mandible left canine, maxillary left canine and mandible left lateral discriminate sex and race.